Toward Optimization of Precast Concrete Factory based on Digital Twin Technology - Moon, Jae Sang; Park, Hyunwook; Kim, Jinyoung (Journal of the Architectural Institute of Korea, 2023)
Rising labor and material costs have led to the use of precast concrete (PC) methods in the construction industry. Since the PC manufacturing process requires maximum productivity while maintaining the required level of safety, the parameters of the PC factory need to be investigated and optimized but are often overlooked. To maximize productivity and safety in PC manufacturing, the parameters of a PC factory were studied using a digital twin developed with the Unreal Engine. The digital twin included a realistic 3D model of the factory, equipment, and workers based on benchmarked factory data. The twin was then used to analyze productivity and simulate worker movements using AI sight, SetLabel, and heatmap features to improve the factory layout. The results demonstrated that digital twins can greatly enhance the analysis, simulation, and optimization of PC factory manufacturing processes.
Keywords: Digital Twin; Precast Concrete Factory; Productivity Analysis; Safety Assessment; Unreal Engine